Soil Moisture and Litter Coverage Drive the Altitude Gradient Pattern of Soil Arthropods in a Low-Elevation Mountain - Haiming Qin; Jingwen Shang; Qin Qi; Bo Cao; Yong Kong; Yujian Li; Junfeng Chen; Xianfeng Yi (Diversity, 2024)
This study sought to investigate the vertical distribution pattern of the soil faunal community in a low-altitude mountain area. On 8 July 2022, a low hill was selected as the study area, and soil arthropods were collected through traps. The leaf litter, vegetation type, and distribution quantity of each sampling site were investigated while the soil faunae were collected. In addition, the soil’s physical and chemical parameters were measured. The results of a one-way ANOVA showed that there were significant differences (p < 0.05) in the soil properties, leaf litter, and plant quantities at different altitudes within the research area. A total of 1086 soil arthropods, belonging to five classes and ten orders, were collected during the study period. The dominant species of soil arthropods at different altitudes were significantly different. The dominant species in low-altitude areas were Armadillidium sp. and Aethus nigritus. However, Eupolyphaga sinensis and Philodromidae were the dominant species in high-altitude areas. The results of a non-metric multidimensional scaling (NMDS) analysis showed that the soil faunae at different altitudes were clustered into two communities: a high-altitude community and a low-altitude community. With the increase in altitude, the species richness of the soil arthropods gradually decreased, and their abundance showed a decreasing trend. A redundancy analysis (RDA) of the soil arthropods and environmental factors showed that soil moisture (p < 0.01), pH (p < 0.01) and defoliation (p < 0.05) had significant effects on the distribution of the soil fauna. The results of a Pearson correlation analysis indicated that different environmental factors had interactive effects on the distribution of the soil arthropods. The quantity and species richness of the soil arthropods in different sample lines were tested using a variance analysis. The results showed that there were significantly smaller quantities of soil arthropods in the sampling line closer to the trekking ladder. This indicates that human tourism, namely mountaineering activities, had a direct impact on the soil fauna. This study can provide a reference for and data support in the development of biodiversity conservation measures for forest parks in low mountain areas.